Optimalisasi Media Digital untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran PAI di MTs Ma’arif NU Sukodadi - Rahmatika, Noviana Dwi; Muharromah, Via Lailatul (Jurnal Murid, 2025)
This research explores the optimization of digital media to increase the learning interest of Generation Z students in Islamic Religious Education (PAI) subjects at MTs. Ma'arif NU Sukodadi. With a qualitative approach, data is collected through interviews, questionnaires, and observations. The results of the study show that digital media such as learning videos, interactive quiz applications, and online platforms are able to significantly increase students' interest in learning. This media offers a more engaging, interactive, and relevant learning experience to students' digital lives. However, there are obstacles such as limited internet access, technological devices, and the skills of students and teachers in utilizing digital media optimally. To overcome these challenges, training for teachers and the provision of adequate technological infrastructure by schools are needed. With the wise integration of digital media, PAI learning can be more effective, fun, and meaningful, as well as strengthen students' character and faith in the digital era.